Fermion zero modes in a Z2 vortex background - Lozano, Gustavo Sergio (2016)
In this paper we study the zero energy solutions of the Dirac equation in the background of a Z2 vortex of a non-Abelian gauge model with three charged scalar fields. We determine the number of the fermionic zero modes giving their explicit form for two specific Ansätze.